(untitled) - Halliday, M. A. K. (London,New York, 2009)
This is a fascinating, seventh volume in the "Collected Works of M.A.K Halliday" series, on "Studies in English Language". Topics covered in the papers from the section on 'Theoretical foundations' include transitivity, theme-rheme, mood, and modality in English. Other sections include papers on English intonation and grammar including discussion of word order in English and the complex structures typical of informal spontaneous conversation. The grammatical analysis of English also serve to demonstrate the application of linguistics to language teaching."The Collected Works of M. A. K. Halliday" is a series that brings together Halliday's publications in many branches of linguistics, both theoretical and applied (a distinction which he himself rejects), including grammar and semantics, discourse analysis and stylistics, phonology, sociolinguistics, computational linguistics, language education, and child language development.
Keywords: English language,English language,Tiếng Anh; Grammar,Ngữ pháp